New Insights Into Human Hyaluronidase 4/Chondroitin Sulphate Hydrolase - Maciej-Hulme, Marissa L. (Frontiers in Cell and Developmental Biology, 2021)
In this review, the current experimental evidence, literature and hypotheses surrounding hyaluronidase 4 [HYAL4, also known as chondroitin sulphate hydrolase (CHSE)] and chondroitin sulphate (CS) are explored. Originally named for its sequence similarity to other members of the hyaluronidase family, HYAL4 is actually a relatively distinct member of the family, particularly for its unique degradation of CS-D (2-O-, 6-O-sulphated CS) motifs and specific expression. Human HYAL4 protein expression and structural features are discussed in relation to different isoforms, activities, potential localisations and protein-protein interaction partners. CS proteoglycan targets of HYAL4 activity include: serglycin, aggrecan, CD44 and sulfatase 2, with other potential proteoglycans yet to be identified. Importantly, changes in HYAL4 expression changes in human disease have been described for testicular, bladder and kidney cancers, with gene mutations reported for several others including: leukaemia, endometrial, ovarian, colorectal, head and neck, stomach, lung and breast cancers. The HYAL4 gene also plays a role in P53 negative human cancer cell proliferation and is linked to stem cell naivety. However, its role in cancer remains relatively unexplored. Finally, current tools and techniques for the detection of specific HYAL4 activity in biological samples are critically assessed. Understanding the role of HYAL4 in human diseases will fortify our understanding of developmental processes and disease manifestation, ultimately providing novel diagnostic opportunities and therapeutic targets for drug discovery.